2007
DOI: 10.1302/0301-620x.89b8.19132
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of benign bone tumours using external fixation

Abstract: We present a retrospective study of patients suffering from a variety of benign tumours in whom external fixators were used to treat deformity and limb-length discrepancy, and for the reconstruction of bone defects. A total of 43 limbs in 31 patients (12 male and 19 female) with a mean age of 14 years (2 to 54) were treated. The diagnosis was Ollier's disease in 12 limbs, fibrous dysplasia in 11, osteochondroma in eight, giant cell tumour in five, osteofibrous dysplasia in five and non-ossifying fibroma in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…The outcomes were similar to other series reported in the literature. [8][9][10]13,15,[20][21][22][23][24][25][26]41 This is the largest series in the English language orthopaedic literature of tibial nonunions treated with the TSF. Feldman et al 10 reported their experience with the TSF for 18 nonunions and malunions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes were similar to other series reported in the literature. [8][9][10]13,15,[20][21][22][23][24][25][26]41 This is the largest series in the English language orthopaedic literature of tibial nonunions treated with the TSF. Feldman et al 10 reported their experience with the TSF for 18 nonunions and malunions.…”
Section: Discussionmentioning
confidence: 99%
“…Once contact and compression at the nonunion site were achieved, additional stabilization of the TSF was accomplished by adding rods or additional struts to lock the frame. Precise deformity correction [41][42][43][44][45] and ease of use 43,44,46 have been cited by other authors as advantages of the TSF. Kristiansen et al 46 showed that the external fixation index was comparable between the TSF and the classic Ilizarov frame.…”
Section: Discussionmentioning
confidence: 99%
“…The fractures usually spontaneously heal and it seems logical to allow that to happen before trying to insert external fixators, internal metallic devices, autograft bone, or allograft chips with or without cement unless the lesions are in a site at risk for deformity [1,15,23,39,60]. The principal site where the limb may be at risk is the proximal femur.…”
Section: Treatment Of Patients With Fcd Nof and Jaffe-campanacci Synmentioning
confidence: 99%
“…We have been using distraction osteogenesis, a biological approach for repairing segmental bone defects, since 1990. Distraction osteogenesis can regenerate bone of sufficient strength and can preserve limb function [11][12][13][14][15][16][17][18]. Little has been reported about the long-term functional outcomes of patients who undergo distraction osteogenesis to reconstruct bone defects caused by excision of bone tumors.…”
Section: Introductionmentioning
confidence: 99%